Timing of postoperative radiation therapy and survival in resected salivary gland cancers: Long-term results from a single institution. (December 2021) - Romine, Perrin E.; Voutsinas, Jenna; Wu, Vicky; Tratt, Micah; Liao, Jay; Parvathaneni, Upendra; Barber, Brittany; Dillon, Jasjit; Timoshchuk, Mari-Alina; Futran, Neal; Houlton, Jeffrey; Laramore, George; et al.
Highlights: In a single institution study, median time to PORT start was 61 days. Within this high-risk population, 10-year OS and LRFS estimates were 61% and 53%. In multivariate analysis, time to PORT start was not associated with OS, LRFS, or DFS. Nodal involvement, grade, size, and age were associated with survival outcomes. Abstract: Objectives: Timely administration of postoperative radiation therapy (PORT) impacts oncologic outcomes in resected squamous cell carcinomas of the head and neck. Salivary gland cancers (SGCs) are uncommon, and timing of PORT has not been extensively explored. We aimed to determine if the interval between surgery and PORT impacts outcomes in SGCs. Materials and Methods: This is a retrospective study of patients with SGCs who underwent curative intent surgical resection followed by adjuvant PORT. Locoregional recurrence free survival (LRFS), disease free survival (DFS), and overall survival (OS) were estimated using the Kaplan Meier method. A multivariate analysis explored the association between demographics, tumor characteristics, and PORT timing with oncologic outcomes using a stepwise Cox proportional hazards model. Results: 180 eligible patients were identified. The median time to PORT start was 61 (range 8–121) days. 169 (93.5%) of patients received neutron radiation. With a median follow up of 8.2 years in surviving patients, the 10-year OS and LRFS estimates were 61% and 53%. In a multivariate analysis, nodal involvement, histologic grade, and age at diagnosis were associated with OS, while nodal involvement, tumor size, and age at diagnosis were associated with LRFS and DFS. Time to PORT start or completion was not statistically associated with survival outcomes. Conclusion: SGC patients who underwent surgery in our tertiary institution received PORT within a median of 61 days after surgery. With long term follow up, PORT timing in this retrospective series was not associated with worse oncologic outcomes, and support timely administration of PORT.